Comparative Activity of Daptomycin and Teicoplanin against Enterococci Isolated from Blood and Urine. (1992) - Forward, Kevin R; DeGagne, Patricia; Bartlett, Kathryn R; Harding, Godfrey K
Abstract : The authors compared the activity of daptomycin with that of ampicillin, penicillin, teicoplanin and vancomycin against 304 strains of Enterococcus species isolated from blood and urine. Daptomycin was as active as penicillin against Enterococcus faecalis : 90% of strains were inhibited by 2 mg/L. Daptomycin was more active than vancomycin (90% minimal inhibitory concentration [MIC90 ] 2 mg/L; 90% minimal bactericidal concentration [MBC90 ] 8 mg/L) but was less active than teicoplanin (MIC50 0.25; MBC90 8 mg/L) or ampicillin (MIC90 1 mg/L; MBC90 2 mg/L) against E faecalis . In time-kill studies daptomycin was not more rapidly bactericidal than ampicillin or penicillin but was significantly more rapidly bactericidal than either teicoplanin or vancomycin. In combination with gentamicin, daptomycin has activity similar to that of penicillin, vancomycin and teicoplanin. Daptomycin may be a suitable alternative to penicillin in patients allergic to penicillins or for the treatment of enterococcal infections caused by beta-lactamase-producing enterococci.